EARLY PERMIAN FUSULINIDS FROM THE CENTRAL PAMIR - ERNST LEVEN (Rivista Italiana di Paleontologia e Stratigrafia, 2017)
An endemic fusulinid assemblage is herein first described from Sakmarian rocks of the Central Pamir. It consists of 42 species and subspecies belonging to the genera Pseudofusulina, Sphaeroschwagerina, Paraschwhagerina, Zellia, Robustoschwagerina, Eoparafusulina, Schubertella, Pseudoendothyra and Pseudoreichelina; 24 species and subspecies are newly named. Comparative studies of the above assemblage and the fusulinid fauna from other regions show that the former is characteristic of the peri-Gondwana area of the Tethys. The endemic elements recognized in the assemblage apparenrly are related to climatic factors.